A short guide to ethical risk - Rotta, Carlo Patetta (Short guides to business risk series., 2010)
Written by a professional with diverse international experience in auditing and fraud, this guide provides an overview of the most significant theories of ethics that have impacted today's business world. It identifies the risks arising from a lack of attention to ethics, particularly in relation to governance, due diligence, reckless business models and other activity that increases exposure to fraud and corruption.